Turn Taking Analysis Of Debate Forums In Indonesia Lawyer Club And Indonesia Lawak Klub - Untari, Vivi Rizqi (2015)
This study investigates how turn taking occurs in Indonesia Lawyer Club and Indonesia Lawak Klub. This study limits the scope of the study into three main parts which are turn taking rules, overlaps and the analysis of repair. This study refers to the theory of conversation analysis by Liddicoat (2007). The data for this study is taken from recorded videos of Indonesia Lawyer Club and Indonesia Lawak Klub which are transcribed into writing form using transcription convention by Jefferson. This study reveals three main findings. The first one is that all turn taking rules are found in both data and the most used rules in ILC is current speaker selects the next speaker (CS2TNS) and the most used rules in ILK is Self-Select (SS). The second is that unproblematic overlaps are most found than problematic overlaps. The number of unproblematic and problematic overlaps in ILC and ILK is not quite different although unproblematic overlaps are mostly found in ILK. The third is that repair in both programs does not simply to correct the mistakes but also as the tool of defending and offending argument and also trading insults. Penelitian ini bertujuan untuk bagaimana turn taking muncul pada Indonesia Lawyer Club dan Indonesia Lawak Klub. Fokus penelitian ini ada pada tiga bagian utama yaitu turn taking rules, overlaps, dan analisis repair. Penelitian ini merujuk pada teori conversation analysis oleh Liddicoat (2007). Data pada penelitian ini diambil dari video rekaman dari acara Indonesia Lawyer Club dan Indonesia Lawak Klub yang kemudian ditranskrip ke dalam bentuk tulisan menggunakan konvensi Jefferson. Ada tiga temuan yang diungkap dalam penelitian ini. Pertama adalah bahwa semua rules dalam turn taking muncul pada kedua data dan pada ILC CS2TNS rule paling banyak muncul, sedangkan pada ILK rule SS muncul paling banyak. Kedua, pada kedua data unproblematic overlaps lebih banyak ditemukan dari pada problematic overlaps. jumlah unproblematic overlaps pada ILC dan ILK tidak terlalu banyak berbeda meskipun jumlah unproblematic overlaps pada ILK lebih banyak dari pada pada ILC. Ketiga, repair pada kedua program memiliki tujuan bukan hanya untuk correcting, tetapi juga memiliki maksud lain yaitu untuk menyerang dan mempertahankan sebuah argument dan juga sebagai alat untuk saling melempar ejekan.